Gray, Wendell. Interview about the Gray stage and fishing from Quidi Vidi. - Sawden, Kari (2013)
Interview with Wendell Gray by Kari Sawden, with Klara Nicter managing the recording equipment, discussing the original and rebuilt Gray stages and the tradition of fishing in the Gray family.